Implicaciones jurídicas del algoritmo: derechos intelectuales y privacidad (Tema Central) - Morales Oñate, Diego Alejandro (2021)
This work attempts to reflect on algorithms, their legal nature, and their critical role in law. Pyramidal elements such as personal data, big data, software, and artificial intelligence that create a post-human legal ecosystem ultimately affect social, economic, and legal dynamics. Based on the above elements, reflections are generated about jurisprudence as a fundamental element of this ecosystem. According to the proposed objectives, my focus will be on two main law theories, ius positivism and ius naturalism. The research is theoretical and legislative; therefore, the chosen methodology will mainly be nominalism, but the holistic approach will serve as a transversal method. Along these lines, the techniques used are theoretical style, doctrine analysis, norms, and jurisprudence. It is vital to carry out a reinterpretation, granting a new vision to the regime and legal dogmatics in its relationship with principles and rights. The basic principles of law serve as guides to technological phenomena and allow us to identify the importance of rights such as anonymity or cryptography. The challenge is to reduce inherited exclusion and discrimination through algorithmic regulations reflecting a new ethical, fair, and balanced paradigm, including the peripheral sectors that are not regularly part of the formal data or the establishment.